A dimensão subjetiva da desigualdade racial: significações de pós-graduandos negros sobre o percurso escolar até o doutorado - Silva, Evelyn Fernanda Pinheiro (2020)
According to IBGE (2019) Brazil has almost 210 million inhabitants, 54% of which are black. In addition to making up the ninth position in the hanking of the world economy, on the other hand, it is in tenth place on the inequality scale, bringing significant reflexes to the almost 400 years of enslavement. In addition to the numbers, understanding about the racial inequalities that exist in our society makes us reflect on the construction of the subjectivity of the Brazilian people, considering discrimination and racism as social violence that is the structure of relationships in society, to which the schooling process blacks would be no different. The present study aimed to understand the meanings constituted by black graduate students on their schooling process and life trajectory until reaching the doctorate, to whom through the meanings it was possible to understand the subjective dimension of racial inequality. For the construction of information, conversations were held with two doctor´s degree black students from PUC-SP, of both sexes, being heard separately. The theoretical-methodological basis of Socio-Historical Psychology was used, which is anchored in the historical-dialectical materialist method as well as Lev. Vigotski's contributions. The movement of analysis of the conversations was built through the Pre-indicators, Indicators and Meaning Core that made it possible to reach the participants' subjective senses. Their experiences are revealed charged with psychological suffering, due to racism and racial discrimination that involves the life trajectory of these subjects throughout the schooling process, until graduate school. The family, friends and the network support as a whole were important elements for structuring the breaking of the social barrier, and which somehow made it possible to reach the doctor degree. However, the different facets of structural and institutional racism are present in these spaces, with strong racial tensions. The scientific academy lacks legitimate preparation to deal with the demands of racial relations. Bearing in mind that the population that predominates in these spaces is white, dominant, with historically possessed privileges and has little involviment with racial dynamics. In this sense, there is a need to build and execute public policies that are capable of promoting emancipation and anti-racist combat. With actions from the educational base, involving the white group throughout the process, while being racialized, which has responsibility for this social violence. Especially because we believe that education is a powerful way to deconstruct racism, as it acts as a mediator that allows overcoming the dominant structure and is an important agent in the transformation of social reality